2020
DOI: 10.3389/fmicb.2020.00836
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline and Fluconazole Have a Synergistic Effect Against Cryptococcus neoformans Both in vitro and in vivo

Abstract: In recent decades, the incidence of Cryptococcus neoformans infection, which causes cryptococcosis, has consistently increased. Fluconazole (FLU) is frequently used in the treatment of this disease, mainly in the immunocompromised population, and longterm therapy usually produces drug resistance. Research on antifungal sensitizers has gained attention as a possible means of overcoming this drug resistance. Minocycline (MINO) has an inhibitory effect in vitro on FLU-resistant Candida albicans, and the combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Moreover, we confirmed that the efficacy of VRZ treatment was associated with fewer and less severe tissue lesions in treated animals compared to untreated controls. These results confirm and extend previous studies that used histopathology in models of invasive fungal infections in G. mellonella [25,26]. One limitation of our study is that only one larva was tested for each condition (strain, dose of VRZ and time-point after treatment).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, we confirmed that the efficacy of VRZ treatment was associated with fewer and less severe tissue lesions in treated animals compared to untreated controls. These results confirm and extend previous studies that used histopathology in models of invasive fungal infections in G. mellonella [25,26]. One limitation of our study is that only one larva was tested for each condition (strain, dose of VRZ and time-point after treatment).…”
Section: Discussionsupporting
confidence: 90%
“…MIN has also been shown to synergize with azoles in the treatment of other fungal species. Kong et al (2020) determined that MIN was able to synergize with FLU in vivo and in vitro when treating Cryptococcus neoformans , while Gao et al (2020) reported synergy between MIN and azoles when treating clinically important Aspergillus , Fusarium , and Exophiala dermatitidis isolates. Herein, we explored the synergistic activity of MIN in combination with azoles when treating FLU-resistant C. albicans , C. parapsilosis , C. tropicalis , C. glabrata , and C. auris .…”
Section: Discussionmentioning
confidence: 99%
“…After MICs were determined, the two most active extracts were selected to evaluate their effect in association with nystatin and clotrimazole. The checkerboard method used was the broth microdilution assay, miniaturized in a 96-well plate as described by Kong et al (2020) with slight modifications [ 21 ]. Briefly, 50 µ L of culture media were introduced in each well of the two microplates.…”
Section: Methodsmentioning
confidence: 99%